The Aleph & Other Metaphors for Image Generation - Ramos, Gonzalo; Barraza, Rick; Dibia, Victor; Lo, Sharon (NeurIPS 2022 Workshop on Human-Centered AI, 2022)
In this position paper, we reflect on fictional stories dealing with the infinite and how they connect with the current, fast-evolving field of image generation models. We draw attention to how some of these literary constructs can serve as powerful metaphors for guiding human-centered design and technical thinking in the space of these emerging technologies and the experiences we build around them. We hope our provocations seed conversations about current and yet to be developed interactions with these emerging models in ways that may amplify human agency.